Perception of the oral health risks of passive smoking from traditional cigarettes, electronic cigarettes, and heated tobacco products: A cross-sectional study - Ludovichetti, Francesco Saverio; Zuccon, Andrea; Di Fiore, Adolfo; Zambon, Giulia; Bargan, Adriana; Stellini, Edoardo; Mazzoleni, Sergio (Tobacco induced diseases, 2024)
Tobacco smoke is a major health risk factor for smokers but also for non-smokers due to passive smoking. These risks come from conventional cigarette smoke but also from aerosol produced by electronic cigarettes and heated tobacco products (HTPs). The aim of this study was to investigate population knowledge about the adverse effects of passive smoking from traditional cigarettes, electronic cigarettes, and HTPs. Between February and October 2023, 504 subjects among the general population responded to a questionnaire with 8 questions in Italian, via a link to the Google Forms platform. The questions related to the oral health effects of active and passive smoking. Descriptive analyses of all variables in the questionnaire were performed, and statistical analyses between variables were carried out using the chi-squared test and Fisher's exact test. A large subset of individuals interviewed stated that active smoking is harmful to health and consider active smoking more damaging compared with passive smoking (86.3%). The majority believed that passive smoking of cigarettes is more harmful to oral health than passive smoking of HTPs (79.4%) or electronic cigarettes (e-cigarettes) (84.9%). Results suggest that most people in this study had good knowledge about the adverse effects of active or passive smoking on health; however, knowledge regarding e-cigarettes and HTPs was poor and confused. These results reveal the complexity of perceptions regarding different types of smoking and the need for further research to fully understand the risks associated with each type of passive smoking.